Analysis of Temporal-spatial Characteristics of Coastal Surface Currents in the Lianyungang Based on HFSWR Observations - ZHANG Wenya; PAN Guangwei; QIU Zhongfeng; REN Lei; XU Qing (Renmin Zhujiang)
Based on the surface current data observed by high frequency surface wave radar (HFSWA) near the shore of Lianyungang from January 2019 to December 2019,this paper analyzes the temporal-spatial characteristics of sea surface current.The results show that:as the regular semidiurnal current,the current turns to reciprocating current near the shore in a southwest-northeast direction,with centralized flow in ebb and flow.The reciprocating current weakens from the shore to the sea,as a result,it gradually turns into rotating current.The average major axis of the current ellipse is 44.34 cm/s for M2-component,11.71 cm/s for S2-component,and 12.85 cm/s for MKS2-component.The measured maximum surface current velocity is between 100 cm/s and 199 cm/s,which mainly occurs in autumn and winter,with little difference in space.There are significant seasonal variations in the temporal-spatial characteristics of the sea surface current field,and the velocity vector field has a trend of counterclockwise rotation.The maximum current velocity in this sea area may be between 44 cm/s and 158 cm/s,with the average value of 89 cm/s.In addition,the current velocity gradually decreases from southeast to northwest.